PA-824 Kills Nonreplicating Mycobacterium tuberculosis by Intracellular NO Release - Singh, Ramandeep (2008)
Bicyclic nitroimidazoles, including PA-824, are exciting candidates for the treatment of tuberculosis. These prodrugs require intracellular activation for their biological function. We found that Rv3547 is a deazaflavin-dependent nitroreductase (Ddn) that converts PA-824 into three primary metabolites; the major one is the corresponding des-nitroimidazole (des-nitro). When derivatives of PA-824 were used, the amount of des-nitro metabolite formed was highly correlated with anaerobic killing of Mycobacterium tuberculosis (Mtb). Des-nitro metabolite formation generated reactive nitrogen species, including nitric oxide (NO), which are the major effectors of the anaerobic activity of these compounds. Furthermore, NO scavengers protected the bacilli from the lethal effects of the drug. Thus, these compounds may act as intracellular NO donors and could augment a killing mechanism intrinsic to the innate immune system.